How serving helps leading: mediators between servant leadership and affective commitment - Bai, Mayangzong; Zheng, Xinyi; Huang, Xu; Jing, Tiantian; Yu, Chenhao; Li, Sisi; Zhang, Zhiruo (Frontiers in Psychology, 2023)
Introduction Servant leadership has long been associated with maintaining employee’s affective commitment, yet the underlying mechanism remains unclear. Research from non-western cultures remains scarce. Methods This study sought to fill in such research gap by introducing insights from social exchange theory perspective, and examined two potential mediators (viz., psychological safety and job burnout) with a largescale, representative Chinese sample. Results A total of 931 staffs in a Chinese hospital were surveyed, and structural equation models revealed that psychological safety (indirect effect = 0.052, 95% Bootstrap CI = [0.002, 0.101]) and job burnout (indirect effect = 0.277, 95% Bootstrap CI = [0.226, 0.331]) parallelly (and partially) mediated the effect of servant leadership on affective commitment. Moreover, these effects held the same between permanent and temporary staffs, as well as between male and female staffs. Discussion Results suggested that a leader’s orientation to care, validate, and respond to their followers’ needs was effective in creating a psychological safe environment and downplaying job burnout in workplace, in exchange to which, followers remained affectively committed to their organization in a long term. Not only did this study contribute to existing literature by providing non-western data for service leadership research, it also provided a deeper understanding of associated mechanisms of how servant leadership might cast on talent retain and organizational development in a long term. These mechanisms shed light on how serving helps leading and advocate servant leadership for hospitals, as well as other serving organizations.